Numerical model for the thermal yield estimation of unglazed photovoltaic-thermal collectors using indoor solar simulator testing. (October 2017) - Katiyar, Munish; van Balkom, Martijn; Rindt, Camilo C.M.; de Keizer, Corry; Zondag, Herbert A.
Highlights: Indoor and outdoor performance testing of unglazed PVT collectors was carried out. Detailed steady state numerical model for unglazed PVT collectors was developed. Reflected long wave radiation from the solar simulator is included in the model. Impact on thermal and electrical output due to the spectral mismatch is considered. Steady state thermal efficiency curves are derived from the numerical model. Abstract: It is a common practice to test solar thermal and photovoltaic-thermal (PVT) collectors outdoors. This requires testing over several weeks to account for different weather conditions encountered throughout the year, which is costly and time consuming. The outcome of these tests is an estimation of the thermal performance characteristics of the collector. Collector performance parameters can be derived with less effort by indoor testing under a solar simulator. However, in case of unglazed PVT collectors the thermal and the electrical performance is affected by two phenomena-additional long wave radiation (3000 nm and greater) due to emissions and reflections from the high temperature artificial sky, and an energy content of the PV spectrum (300–1100 nm) that differs from the global solar spectrum (300–2500 nm). These differences from the reference AM 1.5 solar spectrum lead to errors in the estimation of collector thermal and electrical performance. Therefore, results of indoor performance tests must be corrected to obtain the output of an unglazed PVT collector in real outdoor environment. In this paper a method is proposed to estimate the real thermal performance of unglazed PVT collectors, by using a compact indoor solar simulator testing in combination with a detailed steady state numerical PVT collector model. The numerical model takes into account the physical and spectral attributes of the solar simulator and is used to correct for the unwanted phenomena to derive the actual outdoor collector performance. The resulting numerical model also offers detailed understanding of the collector and can therefore be used to optimise the design of the collector. Furthermore, this model is used to derive thermal performance characteristics of the unglazed PVT collector as defined by solar thermal testing standards, which can be used in system simulation tools (E.g. TRNSYS models) to obtain annual collector and system yields.